Sex-based differences in TB treatment compliance: A mediating factor for sputum conversion among newly diagnosed pulmonary TB patients in Chennai, South India - Yuvaraj Krishnamoorthy; Selvaraja C; Dhanajayan Govindan (Heliyon, 2024)
Background: Tuberculosis (TB) remains a global health concern, particularly in India, which carries a significant portion of the global burden. The role of sex as a determinant of health is increasingly recognized, impacting various aspects of TB, including treatment compliance and outcomes. This study aimed to determine the mediating role of treatment compliance in the relationship between sex and sputum conversion in newly diagnosed pulmonary TB patients in Chennai, South India. Methods: We conducted a retrospective cohort study among patients newly diagnosed for TB at ESIC Medical College & PGIMSR between April 2020 and April 2022. A causal mediation analysis was performed to identify the direct and indirect effects of sex on sputum conversion via the mediator, treatment compliance. We employed logistic regression models and the “paramed” package for the analysis, with bootstrapping technique for examining the significance of indirect and direct effects. Results: The Marginal Total Effect (MTE) suggested that females were more likely to have sputum positivity compared to males (OR: 6.77; p = 0.003). Direct effect of being female increased the odds of sputum positivity at the end of the intensive phase (OR: 3.42; p = 0.03). The indirect effect of being female via treatment compliance significantly increased the odds of sputum positivity at the end of the intensive phase (OR: 1.98; p = 0.03). Conclusion: The study provides evidence that treatment compliance significantly mediates the relationship between sex and sputum conversion in TB patients, highlighting the necessity to consider gendered dimensions of health in TB control strategies.